Low Apgar scores at 5 minutes in a low risk population: maternal and obstetrical factors and postnatal outcome - Salustiano, Eugenia Maria Assunção; Campos, Juliana Alvares Duarte Bonini [UNESP]; Ibidi, Silvia Maria; Ruano, Rodrigo; Zugaib, Marcelo (Associação Médica Brasileira, 2012)
OBJETIVO: Avaliar a associação entre índice de Apgar menor que sete no 5º minuto, os fatores pré-natais e resultados pós-natais. MÉTODOS: Trata-se de estudo retrospectivo com 27.252 recém-nascidos em maternidade escola com população de baixo risco obstétrico, de janeiro de 2003 a dezembro de 2010. Prontuários de todos os casos com índice de Apgar < 7 no 5º minuto (n = 121; - 0,4%) e de 363 casos com Apgar > 7 no 5º minuto, escolhidos ao acaso, foram revisados. Os principais desfechos estudados foram: óbito neonatal, insuficiência respiratória neonatal, necessidade de intubação orotraqueal e de unidade terapia intensiva (UTI) neonatal e encefalopatia hipóxico-isquêmica. RESULTADOS: Após análise de regressão múltipla, desacelerações tardias (DIP II) (OR: 2,4; IC95%: 1,4-4,1) e período expulsivo prolongado (OR: 3,3; IC 95%: 1,3-8,3) se associaram com Apgar < 7 no 5º minuto; assim como com insuficiência respiratória ao nascimento (OR: 3,0; IC 95%: 1,3-6,9), intubação traqueal (OR: 2,5; IC 95%: 1,2-4,8), necessidade de UTI neonatal (OR: 9,5; IC 95%: 6,7-16,8) e encefalopatia hipóxico-isquêmica (OR: 14,1; IC 95%: 3,6-54,7). Nenhuma outra variável prénatal se associou com Apgar < 7 no 5º minuto (p < 0,05). CONCLUSÃO: DIP II e período expulsivo prolongado estão associados com Apgar < 7 no 5º minuto em população obstétrica de baixo risco; situação essa relacionada com maior risco de insuficiência respiratória no parto, necessidade de suporte ventilatório e encefalopatia hipóxico-isquêmica.

OBJECTIVE: To evaluate the association between Apgar scores of less than seven at five minutes (AS5min < 7) and antenatal factors and postnatal outcomes. METHODS: A retrospective cohort and case-control study of 27,252 consecutive term newborns in a low risk obstetrical population between January 2003 and December 2010. Maternal and infant databases were reviewed from all cases with AS5min < 7 (n = 121; 0.4%) and 363 cases with AS5min > 7 at 5 minutes who were randomly selected by a computer program. The main outcomes were neonatal death, newborn respiratory distress, need for orotracheal intubation and neonatal intensive care unit (NICU), and hypoxic-ischemic-encephalopathy. RESULTS: After multiple regression analysis, repeated late decelerations on cardiotocography (OR: 2.4; 95% CI: 1.4-4.1) and prolonged second stage of labor (OR: 3.3; 95% CI: 1.3-8.3) were associated with AS5min < 7, as well as neonatal respiratory distress (OR: 3.0; 95% CI: 1.3-6.9), orotracheal intubation (OR: 2.5; 95% CI: 1.2-4.8), need for NICU (OR: 9.5; 95% CI: 6.7-16.8), and hypoxic-ischemic-encephalopathy (OR: 14.1; 95% CI: 3.6-54.7). No other antenatal factors were associated with AS5min < 7 (p > 0.05). CONCLUSION: Repeated late decelerations and prolonged second stage of labor in the low-risk population are predictors of AS5min < 7, a situation associated with increased risk of neonatal respiratory distress, need for mechanical ventilatory support and NICU, and hypoxic-ischemic-encephalopathy.
Baixos índices de Apgar no quinto minuto de vida em população de baixo risco: fatores maternos e obstétricos e resultados pós-natais
Keywords: Índice de Apgar; parto; asfixia; mortalidade neonatal; encefalopatia hipóxico-isquêmica; Apgar scores; term; asphyxia; neonatal mortality; hypoxic-ischemic-encephalopathy; delivery